PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSETS PADA PT ADARO ENERGY INDONESIA Tbk PERIODE 2013-2022 - Slamet Setiawan, Muhammad; Hidayat, Arif (Journal of Research and Publication Innovation, 2024)
This research aims to examine the influence of the Current Ratio and Debt to Equity Ratio on Return on Assets at PT Adaro Energy Indonesia Tbk for the 2013–2022 period partially and simultaneously. The research method used is to use quantitative methods and propose hypotheses. The population used in this research is the financial report of PT Adaro Energy Indonesia Tbk. and the sample used is the financial report in the form of a balance sheet and profit and loss report for PT Adaro Energy Indonesia Tbk for the period 2013-2022. The data methods used in this research are descriptive statistical analysis, classical assumption test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient test, coefficient of determination test (R2) and hypothesis testing in the form of t test and f test. The research results show that the Current Ratio and Debt to Equity Ratio have no partial effect on Return On Assets. Meanwhile, simultaneous testing shows that the Current Ratio and Debt to Equity Ratio have an effect on Return On Assets. Then an R Square value of 0.163 was obtained which shows that the Current Ratio and Debt to Equity Ratio in explaining the dependent variable Ratio on Assets is only 16.3% while the remaining 83.7% is influenced by other variables not used in this research.